Pengaruh Motivasi Kerja Dan Kompetensi Aparatur Terhadap Kinerja Pelayanan Kartu Tanda Penduduk Elektronik Di Dinas Kependudukan Catatan Sipil Kota Gorontalo - Moningkey, Belinda Injilika (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
Performance is the tangible conduct that each person exhibits as a result of work activities that employees carry out in compliance with their roles and obligations within the company. This study aims to investigate how the Gorontalo City Population and Civil Registration Office's implementation of electronic identity card services is affected both individually and collectively by employee competency and work motivation. A total of fifty employees made up the research sample. The basic data used in this study was gathered via a survey approach. Multiple linear regression approaches were used to analyze the data. The analysis's findings, which yielded a determination coefficient of 62.10%, indicate that: (1) The Gorontalo City Population and Civil Registration Office's electronic identity card services are positively and significantly impacted by work motivation. (2) With a 17.10% determination coefficient, staff competency also significantly and favorably affects the office's electronic identity card services. (3) Both work motivation and civil servant competency have a major impact on the Gorontalo City Population and Civil Registration Office's electronic identity card services. with a coefficient of determination of 79.20%. Leadership, organizational culture, reward and compensation systems, work environment, organizational communication, career development, welfare levels, workload, job satisfaction, job stress, work supervision, and infrastructure and facilities at the service location are all likely to have an impact on the remaining 20.80%.